Evaluation of the Favourable Ecological Impact of the Railway on the Environment - Golubić, Jasna (Promet - Traffic&Transportation, 2012)
The railway has advantages over other branches of longdistancetransportation from the ecological, economic, safety,and technological point of view.The paper gives an evaluation of the favourable influenceof railway traffic on the environment reflected in the rationalenergy consumption, significantly reduced need of physicalspace, and reduced air pollution.Having these data in mind, the railway is considered tohave a negligible influence on environmental pollution. However,studying even such small amounts plays a significant rolein the traffic safety and in the lives of people and nature itself